PERANCANGAN BRAND IDENTITY DAN PROMOSI INBOX - Jessica Stevie Lokito; Pramesti Saniscara (Jurnal Vicidi, 2016)
Inbox is a new business venture in the field of culinary business, specifically in light snacks, such as chocolate, that could be given as gift on special occasions. As a new company, Inbox requires brand identity and promotion strategy in order to raise the market’s awareness of the brand. In order to create a media promotion that is in accordance with the concept and the intended market’s characteristics, the design is done through research using quantitative research methods and will be supported with literature studies as secondary data. Therefore, this research uses the theories in the field visual communication design on brand identity and promotional media.